Intervention Consequences In Brazilian Supplemental Health Market - Sperandio, Luan (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2017)
The rise of interventionism in the private health market in Brazil since the 1990s, through the Law 9.656/1998, the creation of a Regulatory Agency in the sector and through the formation of a jurisprudence that disrespects contracts by mitigating the autonomy of will has caused perverse economic and social repercussions, such as the oligopolization of the sector, shortage in the provision of individual health plans, creation of incentives for the judicialization of actions by the contractors, and the increase in health plans through the establishment of the referential plan minimum, in addition to curtailing free competition.